A Case of Spinal Cord Infarction Following Lumbar Transforaminal Epidural Steroid Injection: MR Imaging and Angiographic Findings - Lyders, E.M. (AJNR Am J Neuroradiol, 2009)
Spinal cord infarction following lumbar transforaminal epidural steroid injection is a rare and devastating complication. We describe the case of a 55-year-old woman who developed spinal cord infarction following right L2-3 transforaminal epidural injection, diagnosed on the basis of clinical and MR imaging findings. Spinal angiography demonstrated occlusion of the right L2 segmental artery with reconstitution of the radicular branch from collaterals. The artery of Adamkeiwicz could not be demonstrated and was presumably occluded by the steroid injection.